Developing Interactive Learning Media of Recount Text Using Articulate Storyline in Teaching Reading Comprehension Skills - Aulia Rahma Nurlita; Acep Haryudin; Arham Mauriyat (IKIP Siliwangi, 2026)
The purpose of this research was to develop interactive learning media using Articulate Storyline and to analyze the feasibility of the developed media as well as teachers’ and students’ responses toward the product. This research used a Research and Development (R&D) method with the ADDIE model. To collect the data, the researcher used several instruments, including document analysis, validation sheets, and questionnaires. The research participants consisted of an English teacher and students of class VIII E at SMPN 3 Parongpong. The obtained data were analyzed through document analysis, expert validation results, and questionnaire responses from both the teacher and students. The findings indicated that the developed media achieved feasibility scores of 86.67% from the first expert and 100% from the second expert, which were categorized as Very Feasible. In addition, positive responses were also shown by the teacher and students, with an average score of 100% and 86.62%, categorized as Very Good. In conclusion, the developed interactive learning media was considered feasible and appropriate to be implemented in English learning activities. These findings suggest that the developed media is suitable to support English learning at the junior high school level.